Performance analysis of multi‐antenna selection policies using the golden code in multiple‐input multiple‐output systems. Issue 12 (1st August 2014) - Ge, Lu; Chen, Gaojie; Gong, Yu; Chambers, Jonathon
Abstract : In multiple‐input multiple‐output (MIMO) systems, multiple‐antenna selection has been proposed as a practical scheme for improving the signal transmission quality as well as reducing realisation cost because of minimising the number of radio‐frequency chains. In this study, the authors investigate transmit antenna selection for MIMO systems with the Golden Code. Two antenna selection schemes are considered: max‐min and max‐sum approaches. The outage and pairwise error probability performance of the proposed approaches are analysed. Simulations are also given to verify the analysis. The results show the proposed methods provide useful schemes for antenna selection.